À quels biens les enseignants veillent-ils ordinairement ? La moralisation des comportements dans les pratiques scolaires d'évaluation - Carole Veuthey; Cynthia d'Addona; Olivier Maulini (Université de Provence, 2018)
Asking schools to take care of children is a sign that pedagogical practices are sometimes suspected of the opposite. Confronting values displayed by public schools in French-speaking Switzerland with ordinary assessment tools of student behavior shows a combination of convergence and divergence between doing good as officially defined vs as locally done by teachers. A cross-induced analysis of variations and regularities between used tools reveals three main expectations: one of social order (obedience, respect for rules) and one of critical thinking (autonomy, participation) corresponding to prescriptive texts; and one of concordance (conviviality, kindness, stability), rather based on direct (and therefore implicit) connivance between compassionate teachers and pupils who are bound to assume failures and frustrations they may encounter. One may ask whether this gap is peculiar to Swiss conveniences or whether all democracies must de facto assume such a tension between an idealized school order and the way it is really moralized.